HIGH ORDER THINKING SKILL (HOTS) IN INTERROGATIVE SENTENCE CONCEPT: THE TEACHERS’ CHALLENGES - Amar Nurjaenul Akbar (Fakultas Keguruan dan Ilmu Pendidikan Universitas Pakuan, 2022)
This research was conducted to determine The Teachers’ Challenges to Construct Higher Order Thinking Skills (HOTS) Question in English Subjects. The purpose of this research is to investigate, collect and analyze data about The Teachers’ Challenges to Construct Higher Order Thinking Skills (HOTS) Question in English Subjects. In this research the researcher used a qualitative method with the teacher as the subject, in obtaining data researchers used Document, questionnaires, and interviews as a way to obtain data. This research was conducted at SMPN 1 Pamijahan, in this research, researchers used observations in the form of attachments to daily test questions, student task and remedial/enrichment made by the teacher as the first step in obtaining data, the second step questionnaire was carried out by giving a questionnaire to the teacher and for the final step is interviewing the teacher.The results of the data collected by the researcher found One of teachers get several challenges in constructing Higher Order Thinking Skills (HOTS) questions in English subject, such as; teacher's lack of understanding of Bloom taxonomy where the bloom is the basis of making HOTS questions, teacher faced problem in making stem and alternative answers in making multiple-choice questions, and problems in dealing with students regarding the HOTS questions given. This problem is a challenge faced by teachers in constructing Higher Order Thinking Skills (HOTS) questions in English subject.